Cashew apple quality by near infrared spectroscopy technique - Samamad, Nancy Taera Ibraimo (Universidade Federal de Viçosa, 2016)
The cashew tree (Anacardium occidentale L.) is a plant with great economic importance for the Brazilian Northeast, due to diversity of products and the amount of jobs generated. Growing demand for healthy products associated an increase in table cashew consumption encouraged the development of technologies to monitor quality criteria. These criteria are determined by destructive analyses, which are usually time-consuming, with high costs and do not take into account the individual cashew variability. Aiming to replace these analyses, the near-infrared spectroscopy (NIRS) allows simultaneous and nondestructive determination of multiple quality attributes. NIRS is a rapid technique that correlates the energy absorption properties in regions of the electromagnetic spectrum with the composition and concentration of molecules through regression models developed by chemometrics. The aim of this study was to develop predictive models in NIRS for bench top and portable device to estimate physical-chemical properties such as firmness, pH, total soluble solids (TSS), soluble sugars (SSC), titratable acidity (TA), flavor, ascorbic acid (vitamin C), carotenoids, total flavonoids, total extractable polyphenols (TEP) and antioxidant activity for monitoring cashew apple quality. For the bench device, the models were constructed with 34 genotypes of 17 samples collected from the reflectance spectra mode. The predictive models obtained for firmness and pH showed determination coefficient values for cross-validation (R2CV) of 0.92 and 0.84, respectively, while for external validation or prediction, coefficients of determination (R2P) were 0.87 for firmness and 0.78 for pH. The residual prediction deviation of cross-validation (RPDCV) have presented values of 3.0 e 2.4 and for external validation values of 2.4 and 2.2 were obtained for firmness and pH, respectively, indicating a good predictive ability. For variables of primary metabolism, the obtained values for R2CV were 0.86 for SSC, 0.83 for TSS, 0.90 for TA and 0.80 for flavor and the R2P values were respectively of 0.78, 0.75, 0.85 and 0.73. The presented RPDCV values were 2.6, 2.4, 3.1 and 2.1 for SSC, TSS, TA and flavor, while RPDP obtained values were 2.0 for SSC and TSS, 3.0 for TA and 1.8 for flavor. In secondary metabolism, models with 0.87 values for R2CV were obtained with R2P of 0.85 for vitamin C. These models presented good ability to predict both cross-validation and external validation with RPDCV and RPDP values of 2.6 and 2.8, respectively. Carotenoids models presented R2CV and R2P values of 0.89 and 0.79, with RPDCV and RPDP of 2.9 and 2.0, respectively, while for total flavonóides, models were obtained with values of 0.86 for both R2CV and R2P as well as RPDCV values of 2.6 and 2.0 to RPDP. Models obtained for TEP has presented values of 0.90 for R2CV and 0.89 to R2P and RPDCV values of 3.2 as well as 2.5 for RPDP. Antioxidant activity models were obtained with R2CV and R2P values of 0.87 and 0.81, respectively, and RPDCV values of 2.7 and 2.2 for RPDP. For portable device predictive models, 75 samples from 21 different genotypes were collected and evaluated of which firmness, pH, TSS, TA, flavor and vitamin C presented R2CV values of 0.77, 0.75, 0.90, 0.85, 0.80 and 0.89, respectively, with the average relative error of -1.1%, 0.2%, 0.5%, -1.3%, 2.6% and 4.9%. For these variables were obtained coefficients of determination values for prediction (R2P) of 0.76, 0.72, 0.88, 0.85, 0.82 and 0.83 with standard error of prediction (SEP) coefficient of variability of 18.2%, 3.0%, 5.6%, 19.6%, 15.4% and 12.1%. Besides these, a quality monitoring experiment in cold storage was evaluated by NIRS over nine days. Four genotypes were used with tree repetitions for TSS, vitamin C and pH assessment evaluated in split plot in time.

O cajueiro (Anacardium occidentale L.) é uma planta de grande importância econômica para o Nordeste brasileiro, pela diversidade de produtos e quantidade de empregos gerados. A crescente demanda por produtos saudáveis associados ao aumento no consumo do caju de mesa incentivou o desenvolvimento de tecnologias para monitorar os critérios de qualidade. Esses critérios são determinados por meio de análises destrutivas, que são normalmente demoradas, com custos altos e não leva em consideração a variabilidade individual do caju. Visando substituir essas análises, a espectroscopia de infravermelho próximo (NIRS) permite a determinação simultânea e não destrutiva de vários atributos de qualidade. NIRS é uma técnica rápida que correlaciona as propriedades de absorção de energia em regiões do espectro electromagnético com a composição e concentração de moléculas através de modelos de regressão desenvolvidos por meio da quimiometria. O objetivo deste estudo foi desenvolver modelos preditivos em NIRS para o dispositivo de bancada e portátil visando estimar propriedades físico-químicas tais como firmeza, pH, sólidos solúveis totais (TSS), açúcares solúveis (SSC), acidez titulável (TA), sabor, ácido ascórbico (vitamina C), carotenóides, flavonóides totais, polifenóis extraíveis totais (TEP) e atividade antioxidante para o monitoramento da qualidade do pedúnculo de caju. Para o dispositivo de bancada, os modelos foram construídos com 34 amostras de 17 genótipos a partir de espectros coletados no modo de refletância. Os modelos preditivos obtidos para firmeza e pH apresentaram valores de coeficiente de determinação para validação cruzada (R2CV) de 0.92 e 0.84, respectivamente, enquanto que para os coeficientes de determinação para a validação externa (R2P) foram de 0.87 para firmeza e 0.78 para pH. A relação do desempenho do desvio para validação cruzada (RPDCV) apresentaram valores de 3.0 e 2.4 e, para a validação externa (RPDP) se obtiveram valores de 2.4 e 2.2 para firmeza e pH, respectivamente, indicando boa capacidade de predição. Para as variáveis do metabolismo primário, os valores obtidos para o R2CV foram de 0.86 para SSC, 0.83 para TSS, 0.90 para TA e de 0.80 para sabor, sendo que os valores de R2P foram de 0.78, 0.75, 0.85 e 0.73, respectivamente. Os valores apresentados para RPDCV foram, respectivamente, de 2.6, 2.4, 3.1 e 2.1 para SSC, TSS, TA e sabor, enquanto que os valores de RPDP foram de 2.0 para SSC e TSS, 3.0 para TA e 1.8 para sabor. No metabolismo secundário, foram obtidos modelos com valores de 0.87 para R2CV e de 0.85 R2P para vitamina C, apresentando boa capacidade de predição tanto para validação cruzada como para validação externa, com valores de RPDCV e de RPDP de 2.6 e 2.8. Para carotenoides, modelos com R2CV e R2P de 0.89 e 0.79 foram obtidos, com RPDCV e de RPDP 2.9 e 2.0, respectivamente, enquanto que para flavonóides totais, foram obtidos valores de 0.86 para ambos R2CV e R2P e, valores de RPDCV de 2.6 e de 2.0 para RPDP. Modelos obtidos para TEP tiveram valores 0.90 para R2CV e de 0.89 para R2P, bem como valores de RPDCV de 3.2 e 2.5 de RPDP, sendo que para atividade antioxidante foram obtidos modelos com valores de R2CV e R2P de 0.87 e de 0.81, respectivamente, com valores de RPDCV de 2.7 e 2.2 para RPDP. Para o dispositivo portátil, foram obtidos modelos preditivos de 75 amostras provenientes de 21 diferentes genótipos sendo que para firmeza, pH, TSS, TA, sabor e vitamina C os valores de R2CV foram de 0.77, 0.75, 0.90, 0.85, 0.80 e 0.89, respectivamente com a média do erro relativo de -1.1%, 0.2%, 0.5%, -1.3%, 2.6% e 4.9%. Para essas variáveis, foram obtidos valores de coeficientes de determinação para previsão (R2P) de 0.76, 0.72, 0.88, 0.85, 0.82 e 0.83 com os coeficientes de variabilidade do erro padrão de previsão (SEP) de 18.2%, 3.0%, 5.6%, 19.6%, 15.4% e 12.1%. Além destes, realizou-se um experimento de monitoramento de qualidade do caju de mesa refrigerado por NIRS ao longo de nove dias. Foram utilizados quatro genótipos com três repetições onde se avaliou TSS, vitamina C e pH analisados em parcelas subdividida no tempo.
Qualidade do pedúnculo de caju por técnica de espectroscopia de infravermelho próximo
Keywords: Annacardium occidentale; Cajú - Tecnologia pós-colheita; Cajú - Qualidade; Cajú - Propriedades físico-químicas; Espectroscopia de infravermelho; Ciências Agrárias; Fisiologia de Plantas Cultivadas